High-Impact Practices in the First Year: Access and Quality for Underserved Students. - Wenger, Kevin (Experiential Learning and Teaching in Higher Education, 2025)
This study investigates two HIPs in the first year of college, a significant time of transition, focusing on levels of quality and barriers to participation for underserved students. Results indicate that significant barriers to participation persist, particularly for those from underserved backgrounds. When they do participate, some underserved students report higher quality HIPs, suggesting additional benefits. These results highlight the importance of attention to both barriers and quality for HIPs to fulfill their potential for students of all backgrounds.